THE OLDEST ROCKS ON EARTH: TIME CONSTRAINTS AND GEOLOGICAL CONTROVERSIES - Kamber B.S.; Moorbath S.; Whitehouse M.J. (My University, 2001)
Ages in the range 3.6-4.0 Ga (billion years) have been reported for the oldest, continental, granitoid orthogneisses, whose magmatic precursors were probably formed by partial melting or differentiation from a mafic, mantle-derived source. The geological interpretation of some of the oldest ages in this range is still strongly disputed. The oldest known supracrustal (i.e. volcanic and sedimentary) rocks, with an age of 3.7-3.8 Ga, occur in West Greenland. They were deposited in water, and several of the sediments contain (13)C-depleted graphite microparticles, which have been claimed to be biogenic. Ancient sediments (c. 3 Ga) in western Australia contain much older detrital zircons with dates ranging up to 4.4 Ga. The nature and origin of their source is highly debatable. Some ancient (magmatic) orthogneisses (c. 3.65-3.75 Ga) contain inherited zircons with dates up to c. 4.0 Ga. To clarify whether zircons in orthogneisses are inherited from an older source region or cogenetic With their host rock, it is desirable to combine imaging studies and U-Pb dating of single zircon grains with independent dating of the host rock by other methods.. including Sm-Nd, Lu-Hf and Pb/Pb. Initial Nd, Hf and Pb isotopic ratios of ancient orthogneisses are essential parameters for investigating the degree of heterogeneity of early Archaean mantle. The simplest interpretation of existing isotopic data is for a slightly depleted, close-to-chondritic, essentially homogeneous early Archaean mantled this does not favour the existence of a sizeable, permanent continental crust in the early Archaean. By analogy with the moon, massive bolide impacts probably terminated on Earth by c. 3.8-3.9 Ga, although no evidence for them has yet been found. By c, 3.65 Ga production of continental crust was well underway, and global tectonic and petrogenetic regimes increasingly resembled those of later epochs.
Keywords: oldest rocks